ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI MINAT PEMANFAATAN DAN PENGGUNAAN APLIKASI MOKA POS (POINT OF SALE) BERBASIS CLOUD PADA UMKM DI KOTA SEMARANG DENGAN MENGGUNAKAN MODEL UNIFIED THEORY OF ACCEPTANCE AND USE OF TECHNOLOGY (UTAUT) - Rahminawati Ilma; Dul Muid (Diponegoro Journal of Accounting, 2023)
The purpose of this study is to identify the factors that influence the acceptance and use of the Moka Point of Sale (POS) application for MSMEs in Semarang City. This study uses the variables of performance expectancy, effort expectancy, social influence, and facilitating conditions based on the Unified Theory of Acceptance and Use of Technology (UTAUT) model by Venkatesh et al (2003). This research uses primary data obtained from questionnaires distributed to MSME owners in Semarang City who are using Moka POS in running their business. By using purposive sampling technique in sample selection, 100 research samples were obtained. The data analysis technique used the Structural Equation Model - Partial Least Square (SEM-PLS) with a data processing application program, namely SmartPLS 3.3.3.The results showed that the variable performance expectations has a positive and significant effect on the behavioral intention, and the behavioral intention also has a positive and significant effect on the use behavior of Moka POS application. While the variables of effort expectancy and social factors have no effect on the interest in using the Moka POS application. The facilitating condition variable was also stated to have no influence on the use behavior of Moka POS application. The results of this research contributed theoretical and practical contributions to behavioral accounting.